IoRT enabled gesture mimicking Robotic Hand based on Computer Vision - Javeed, Yasir; Mehdi, Hafiz Muhammad (2024 International Conference on Emerging Trends in Smart Technologies (ICETST), 2024)
Human Robot Interaction (HRI) is a multi-model, progressive approach where humans get together with robots to complement one another. The Internet of Robotic Things (IoRT) happens to be an intriguing technology of the modern world, but it becomes immersive when combined with computer vision. IoRT refers to the control of robots over the internet. According to the International Labor Organization (ILO), close to 3 million people die each year due to occupational hazards. Explosives, munition, chemical processing, and mining industries are in the midst of pernicious industries. This paper presents a human gesture-controlled robotic hand that uses MediaPipe and OpenCV libraries to classify gestures and proposes an IoRT architecture. The Cortex M0+ based Raspberry Pi Pico MCU has been used to realize the concept of AI on embedded systems where a worker makes a robotic entity to mimic him while sitting in a safe cabin, eliminating the need for numerous sensors and cumbersome wearables.